Barriers to breast cancer treatment in Brazil: A study on migration and regional disparities - Marcelo Antonini; Gabriela Moreira Santos; André Mattar; Marina Diogenes Teixeira; Andressa Gonçalves Amorim; Marina Fleury de Figueiredo; Marcellus do Nascimento Moreira Ramos; Francisco Pimentel Cavalcante; Eduardo Camargo Millen; Antonio Luis Frasson; Felipe Zerwes; Odair Ferraro; et al. (Public Health in Practice)
Background: Breast cancer (BC) is one of the most prevalent cancers globally, with 2.3 million new cases annually in 2023. In Brazil, it is estimated that there are 74,000 new cases per year, representing 20.3 % of cancers in women in the country. Limited access to adequate treatment forces patients to seek care elsewhere, straining the healthcare system and delaying treatment initiation. This study aimed to determine the migration rate of BC patients in Brazil and specifically to analyze migration rate by stage and treatment modality, as well as its costs and possible reasons for delays. Study design: A cross-sectional observational ecological study was conducted using retrospective data on the prevalence of breast cancer in Brazil, including the number of diagnoses and treatments in each state. The study evaluated patient migration rate for treatment, with information obtained from the DATASUS - SISCAN/Cancer Information System database. The selected analysis period was from 2017 to 2022, during which all necessary variables were available. Results: Among the 275,140 cases analyzed, 98.18 % were women. The national migration rate was 2.12 %, ranging from 0.35 % in the Northeast to 9.31 % in the Midwest. Stage IV had the highest migration rate (1.74 %), and migration rate for radiotherapy was significant in some states, reaching 100 % in specific cases. Conclusion: The migration rate of BC patients for treatment in Brazil shows significant regional variations, with higher rates in the Midwest and lower rates in the South. Some states exhibited a 100 % migration rate for access to radiotherapy. Stage IV patients are the most prone to migrate, and the search for radiotherapy can lead patients to move to other states. These results highlight the need for specific health policies to ensure access to treatment across the country.